Comparison of Behavioral Responses to Manual Restraint Tests in Two Breeds of Japanese Native Chicken - Oka, T.; Bungo , T. (International Journal of Poultry Science, 2014)
The aim of the present study was to evaluate the characteristic of two native Japanese chicken breeds, Uzurao (UZ) and Chabo (CB) using two types of manual restraint tests for the detection of fearfulness. Each hen was grabbed by one hand or held in an underarm with mild pressure, whereas the other hand was used to restrain the legs. Thereafter, latencies to the first struggle and frequencies of struggling were recorded. The latency in UZ was shorter than that in CB (p